Research on tax compliance incentive effects of platform companies from the perspective of incomplete contract: An empirical study based on China - Xuefeng Shao; Shi Chen (Amfiteatru Economic, 2024)
In this paper, based on the incomplete contract perspective, we select the implementation of the Electronic Commerce Law of the People's Republic of China as a quasi-natural experiment to study the tax compliance incentive effects of platform firms. Our study finds that the Chinese experience helps to improve the efficiency of tax compliance contract enforcement and significantly increases the propensity of platform firms to comply with taxes. Of course, these effects are also constrained by the contractual environment, social responsibility, financing constraints, and market competition. Further mechanism tests show that the incompleteness of the tax compliance contract is compensated by two mechanisms of action, namely the reduction of information asymmetry and the reduction of transaction costs of the tax department, which generate tax compliance incentive effects. The research has important implications for optimising the tax compliance contract of platform firms and reducing tax leakage in the platform economy.
Keywords: H26; D86; 330; incomplete contract; platform enterprises; tax compliance; transaction cost